Unia Europejska dziś i jej niepewna przyszłość. Cz.I - Fiszer, Józef M. (Rocznik Integracji Europejskiej, 2015)
There is no doubt that the European Union, which is the result of European integration, is an unprecedented entity in the history of international relations. It is a symbol of a new, united Europe, which, after negative experiences, decided to become a safe continent, and therefore eliminate once and for all war from the life of its states and nations. Unfortunately, the idea of ‘eternal peace,’ which many politicians and philosophers dreamed about, has failed to be fully implemented to this day. Moreover, the recent war in the Balkans and the current Russian-Ukrainian war still make this idea impossible in international relations in Europe. The purpose of this paper is to present the European Union today, ten years after its 2004 enlargement by a further ten countries, including eight from the former Eastern bloc. The paper shows the strengths and weaknesses of the EU, which – although significantly strengthened by the Eastern enlargement – still cannot cope with many economic, political, social and international problems. The author of this paper tries to come up with answers to many questions concerning the present EU: why is this happening, what are the reasons for it and what are the prospects for the EU in the 21st century. The main thesis is that the EU needs overhauling, so it can continue to grow and be an engine of European integration. If this does not happen, though, the EU will begin to crumble and eventually disintegrate, or become no more than a free trade zone.